Isolation and HPLC Analysis of Astilbin in Lysiphyllum strychnifolium (syn. Bauhinia strychnifolia) Stems - Sampaopan, Yupaporn; Kitprapiumpon, Nirawan; Kongkiatpaiboon, Sumet; Duangdee, Nongnaphat; Wongyai, Surapote (Science & Technology Asia, 2021)
Lysiphyllum strychnifolium (syn. Bauhinia strychnifolia), vernacularly known in Thai as “Ya Nang Daeng”, has been traditionally used for detoxification and as an anti fever in Thai traditional medicine. Despite published research on the plant’s phytochemical constituents and their anti cancer activity, quality assessment and pharmacological investigations have been hampered since the major bioactive compound remains unknown. Therefore, in this study, the isolation of a major compound has been explored, and its structure has been elucidated as astilbin. An RP HPLC method was developed and validated for the determination of astilbin in L. strychnifolium stems. The chromatographic separation was performed on a reversed phase C 18 column using gradient system of 2% (v/v) acetic acid and acetonitrile with flow rate of 1 mL·min 1. The UV detection was set at a wavelength of 290 nm. The validated method showed good sensitivity, linearity, precision, and accuracy. The method could be used for routine analysis of astilbin in L. strychnifolium stems going forward. The present study provided a useful basis for the quality control of crude plant material, extract, and phytopharmaceutical products.